Germination parameterization and development of an after-ripening thermal-time model for primary dormancy release of Lithospermum arvense seeds - Chantre Balacca, Guillermo Ruben (2009)
Models based on thermal-time approaches have been a useful tool for characterizing and predicting seed germination and dormancy release in relation to time and temperature. The aims of the present work were to evaluate the relative accuracy of different thermal-time approaches for the description of germination in Lithospermum arvense and to develop an after-ripening thermal-time model for predicting seed dormancy release.